Competitive Strategy Analysis at Nugrah Farma Pharmacy South Konawe Regency - Novianti, Nugrah; Razak, Abdul; Hakim , Abdul (International Journal of Management and Education in Human Development, 2024)
This study aims to find out and analyze (1) Determine and develop alternative competitive strategies that are appropriate for the Company by using analysis and theoretical foundations of management theory.; (2) Obtaining a proposed strategy is expected to restore the level of profit and continue to increase (3) Develop the ability to analyze, understand and determine solutions in solving problems in pharmacies. Based on the results of the study, it can be concluded that (1) Nugrah Farma Pharmacy in South Konawe Regency has implemented a 7P marketing mix strategy, and the results are good for price, product, location, people, physical evidence, and process. However, promotions still need to be improved.; (2) Nugrah Farma Pharmacy in South Konawe Regency is in a favorable strategic position, namely in quadrant I in the swot diagram and in the IE matrix into the cell diagram I (Development and Stability). The strategy that must be implemented is to use internal strengths to take advantage of existing opportunities by creating new strategies that allow the creation of opportunities. This strategy shows that the company is strong and able to defend against various threats (3) WoMaintaining competitive prices, utilizing promotional media, providing continuous consulting services, and providing additional services that can increase customer loyalty are alternative marketing mix strategies that are prioritized to implement.